The Influence of Managerial Ownership and Institutional Ownership on Tobin’s Q and ROA with CSR as a Moderating Variable in Companies Listed on the Jakarta Islamic Index (JII70) - Maghfiroh, Salma Desta Wasilah; Putri Pertiwi, Imanda Firmantyas (Profesional Muda Cendekia Publishing, 2024)
Research Aims: Managerial ownership refers to the ownership of shares held by company management, while institutional ownership is the ownership of shares by institutions such as pension funds and investment companies. Company performance, which is the focus of this study, is important to evaluate because it reflects the efficiency and effectiveness of the company in generating value for shareholders. This study aims to determine the effect of managerial ownership, institutional ownership on Tobin's q, to ​​determine the effect of managerial ownership, institutional ownership on ROA, to determine how managerial ownership, institutional ownership on Tobin's q with CSR as a moderating variable on the Jakarta Islamic Index (JII70) in 2020-2023, and to determine how managerial ownership, institutional ownership on ROA with CSR as a moderating variable on the Jakarta Islamic Index (JII70) in 2020-2023. The technique used is purposive sampling with a sample size of 33 companies. Design/methodology/approach: The technique used is purposive sampling with a sample size of 33 companies. Research Findings: The data analysis technique uses the coefficient of determination (R2), simultaneous significance test, parameter significance test and moderated regression analysis test. Theoretical Contribution/Originality: The results of the study indicate that managerial ownership has a significant negative effect on Tobin's q, Managerial ownership has a positive and significant effect on ROA, Institutional ownership has a positive and significant effect on Tobin's q, Institutional ownership has a significant negative effect on ROA, CSR is unable to moderate the effect of managerial ownership on Tobin's q, CSR is unable to moderate the effect of managerial ownership on ROA, CSR is able to moderate the effect of institutional ownership on Tobin's q, CSR is able to moderate the effect of institutional ownership on ROA.